A case of acute gangrenous cholecystitis in an ectopic left sided gallbladder: a challenging laparoscopic cholecystectomy - Barman, Seema; Kamat, Manmohan; Sharma, Varsha; Sathyan, Jeena; Shetye, Shravani (International Surgery Journal, 2022)
Left sided gallbladder is a rare entity and can be associated with other anomalies of portal vein and biliary system. It can be dangerous as it can create clinical confusion and hence radiological identification with the help of CT scan or USG is of great importance. A 60 years old lady, presented with pain and tenderness in the epigastrium and right hypochondrium, on USG got diagnosed with acute cholecystitis. Intra operatively she was found to have a gangrenous left sided ectopic gallbladder (GB). The incidence of ectopic GB is only 0.1-0.7% and can be found in wide range of locations including the lesser omentum, the retro-duodenal area, falciform ligament, abdominal wall muscles. Mal-positioning of the gallbladder can confound presenting signs and symptoms of the disease creating technical problems during surgical procedures and hence it is advised to always resect it out whenever diagnosed.